Representations about deciding to Major in Education from a Family Discourse and Education Major Perspective - Gómez, Héctor (2019)
The objective of this article is to understand discourse representation in families and their children who decide to major in Education.  This study was conducted among students majoring in Primary School Education at less competitive universities[1]. The combined study, involving two surveys and two case studies based on a sequential and triangulated analysis. The analysis showed that there was no direct relationship between a student´s selected major and career social status. Family support of the students who decide to become Education Majors as well as that of the surrounding context tends to be met with apprehension from the start which increases as students move forward in their studies.  At the same time, students tend to be strongly driven to study Education based on social commitment and believing that they have a teaching vocation.   [1]  A less competitive university refers to academic institutions which, based on Rufinelli (2014), admitted students with a 450 and 549 score on their Entrance Exam. It is important to emphasize that the end scores varied between 150 and 850 points.